African Buffalo Optimization: A Swarm-Intelligence Technique - Odili, Julius Beneoluchi; M. N. M., Kahar; Shahid, Anwar (Elsevier Ltd, 2015)
This paper proposes a new optimization technique called the African Buffalo Optimization. The African Buffalo Optimization (ABO) draws its inspiration from the behavior of African buffalos in the vast African forests and savannahs. African buffalos are a wild species of domestic cattle and are always mobile tracking the rainy seasons in different parts of Africa in search of lush green pastures to satisfy their large appetites. Our interest is in their organizational ability through two basic sounds in search of solutions. Experiments carried out using the novel algorithm in solving some benchmark Travelling Salesman’s Problem when compared with the results from some popular optimization algorithms show that the ABO was not only able to obtain better solutions but at a faster speed.